2018
DOI: 10.1177/0162643418795842
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Independent Participation Within Vocational Activities for an Adolescent With ASD Using AAC Video Visual Scene Displays

Abstract: Adolescents with autism spectrum disorder (ASD) often require support both for learning new skills and for communication. This study used a multiple baseline across activities design to evaluate the effect of videos with integrated visual scene displays (video VSDs), presented using a tablet-based app, on the percentage of steps completed independently within vocational training tasks by an adolescent with ASD and complex communication needs (CCN). Using the video VSDs, the participant met the mastery criterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…All VBIs in the studies reviewed were implemented by the researchers or teachers who took the role of job coach. The studies revealed that VBIs increased independent participation in integrated competitive work settings, which led to less supervision from job coaches (Gentry et al, 2015;Babb et al, 2018). Given that VBIs were reported as easy to implement and validated to have positive results by the employers (Bross et al, 2018;Kellems & Morningstar, 2012;, practitioners can consider supporting co-workers and employers to implement VBIs as a form of support and accommodation to maintain and sustain high quality of job performance.…”
Section: Implications For Practicementioning
confidence: 99%
“…All VBIs in the studies reviewed were implemented by the researchers or teachers who took the role of job coach. The studies revealed that VBIs increased independent participation in integrated competitive work settings, which led to less supervision from job coaches (Gentry et al, 2015;Babb et al, 2018). Given that VBIs were reported as easy to implement and validated to have positive results by the employers (Bross et al, 2018;Kellems & Morningstar, 2012;, practitioners can consider supporting co-workers and employers to implement VBIs as a form of support and accommodation to maintain and sustain high quality of job performance.…”
Section: Implications For Practicementioning
confidence: 99%
“…Except for Riffel et al (2005), all seven studies (e.g., Babb et al, 2019;Cullen et al, 2017) using only video prompting found that participants' performance improved, and Van Laarhoven et al (2018) indicated that participants performed better when they used their preferred device (HP Slate vs. iPad). Participants in studies utilizing video prompting with additional cueing or feedback (Pistoro et al, 2018;Seaman et al, 2018;Seaman-Tullis et al, 2019) all met the target criterion, and they maintained their improved performance during the maintenance and generalization phases.…”
Section: Reported Effectivenessmentioning
confidence: 99%
“…Students may demonstrate personal preferences for particular types of technology (Scherer et al, 2011), and some shopping environments (e.g., a noisy store) may necessitate adaptations to the technology (e.g., the provision of visual supports to complement speech output; Babb et al, in press). Interventionists should consider a feature-matching process to review both low-tech and high-tech options (Satsangi et al, 2019), and to identify technology that will provide an effective, efficient, and socially acceptable support for community participation activities such as grocery shopping (Babb et al, 2019).…”
Section: Discussionmentioning
confidence: 99%